2020
DOI: 10.1021/acsami.0c05416
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Layers with Different Decorative Patterns for Polymer Electrolyte Membrane Fuel Cells

Abstract: To optimize the interface of the catalyst layer (CL) and gas diffusion layer (GDL) in polymer electrolyte membrane fuel cells (PEMFCs), microporous layers (MPLs) with different decorative patterns were prepared. Carbon paper treated with polytetrafluoroethylene was used as a substrate for the coating of MPLs. To accelerate water removal and gas permeation, ammonium chloride was utilized to improve the porous structure of MPLs. Owing to the recrystallization and pyrolysis of ammonium chloride with different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…The effect of the nature of the substrate, carbon black, and PTFE loading in the different carbonaceous phases in the microporous layer (MPL) is usually chosen to modify their surfaces with hydrophobic materials for better H 2 O removal ability [ 389 , 390 ]. The effect of the hydrophobicity of microporous layers with different decorative patterns to optimize the interface of the catalyst layer and gas diffusion layer (GDL) in the performance of PEMFC was investigated [ 391 ]. Results concluded that the microporous layer could be considered as a promising strategy to improve the mass transfer efficiency at the interface of the catalyst layer and gas diffusion layer.…”
Section: Hydrophobicity Of Electrodes and Gas Diffusion Layersmentioning
confidence: 99%
“…The effect of the nature of the substrate, carbon black, and PTFE loading in the different carbonaceous phases in the microporous layer (MPL) is usually chosen to modify their surfaces with hydrophobic materials for better H 2 O removal ability [ 389 , 390 ]. The effect of the hydrophobicity of microporous layers with different decorative patterns to optimize the interface of the catalyst layer and gas diffusion layer (GDL) in the performance of PEMFC was investigated [ 391 ]. Results concluded that the microporous layer could be considered as a promising strategy to improve the mass transfer efficiency at the interface of the catalyst layer and gas diffusion layer.…”
Section: Hydrophobicity Of Electrodes and Gas Diffusion Layersmentioning
confidence: 99%
“…As the MPS, a carbon paper (TGP-H-060, Toray) was treated with a poly(tetrafluoroethylene) (PTFE) suspension (DISP30, DuPont) to avoid flooding in the interlaced carbon fibers. 30 The MPL slurry was obtained by mixing acetylene black and PTFE suspension in deionized water with a mass ratio of 7:3. The additive amount of CeO 2 in the above slurry was 10 wt %.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, MPLs with a porosity gradient experience internal capillary pressure. Similarly, other researchers have shown that MPLs with a porosity gradient introduced using ammonium chloride exhibit electrochemical performance superior to that of MPLs with a uniform pore-size distribution. The addition of thermally expandable GPs has been reported as another approach for the fabrication of MPLs with a porosity gradient . MPLs with gradient hydrophobicity have also been effective for draining water accumulated in GDLs .…”
Section: Introductionmentioning
confidence: 97%
“…MPLs with gradient hydrophobicity have also been effective for draining water accumulated in GDLs . To fabricate MPLs with gradient features requires at least one step of the wet-coating process to be repeated. ,, However, repeated drying and annealing processes for the fabrication of multilayers significantly increase the product cost and the environmental impact.…”
Section: Introductionmentioning
confidence: 99%